Research and Development of Modified Building Materials - Stefanidou, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint includes research papers on different disciplines related to composites. It contains research related to new topics such as nanotubes, fibres, admixtures added in cement and concrete. Additionally self-healing and self-sensing issues are presented. Environmental, and thermal-related topics are also discussed. Studies related to consolidation topics and alkali activation of clays are included. This blend of traditional and modern building materials, all having a common ground, the use of new technologies for improving fresh and harden state properties, make this volume interesting.